The fundamental right to health in Colombia: a legal and jurisprudential case study - Grandas Ardila, Erika Vianneth (DIXI, 2024)
Topic and Scope: The fundamental right to health is autonomous and inalienable, both individually and collectively. It encompasses timely, effective, and high-quality access to health services for the preservation, improvement, and promotion of health. Characteristics: Colombia is a social state governed by the rule of law. Findings: The Preamble to the 1991 Political Constitution establishes guaranteeing the life of its citizens as one of the essential purposes of the Colombian State. Furthermore, the protection of the right to life is enshrined in Article 11 of the aforementioned Political Constitution as a fundamental right. Its effective and comprehensive fulfillment, as the right to a dignified life, depends on the real guarantee of other rights. Among these, the right to health stands out. Articles 48 and 49 of the Constitution were further developed by Law 100 of 1993, which, among other things, structured the General System of Social Security in Health. The General System of Social Security in Health (SGSSS) aims to regulate the public health service; create conditions for access to health services at all levels of care for the entire population; cover general illness and maternity contingencies for its members and beneficiaries; and ultimately guarantee all individuals access to health promotion, protection, and recovery services. Conclusion: The right to health has been established as a fundamental right of every individual, as well as a mandatory public service that may be provided by public or private entities under the direction, coordination, and control of the State, with the aim of ensuring its maximum protection.